Low Incidence of Fatigue after Hypofractionated Stereotactic Body Radiation Therapy for Localized Prostate Cancer - Dash, Chiranjeev; Demas, Kristina; Uhm, Sunghae; Hanscom, Heather N.; Kim, Joy S.; Suy, Simeng; Davis, Kimberly M.; Sween, Jennifer; Collins, Sean; Adams-Campbell, Lucile L. (Frontiers in Oncology, 2012)
Background: Fatigue is a common side-effect of conventional prostate cancer radiation therapy. The increased delivery precision necessitated by the high dose per fraction of stereotactic body radiation therapy (SBRT) offers the potential of reduce target volumes and hence the exposure of normal tissues to high radiation doses. Herein, we examine the level of fatigue associated with SBRT treatment. Methods: Forty patients with localized prostate cancer treated with hypofractionated SBRT, and a minimum of 12 months follow-up were included in this analysis. Self-reported fatigue and other quality of life measures were assessed at baseline and at 1, 3, 6, 9, and 12 months post-SBRT. Results: Mean levels of fatigue were elevated at 1 month post-SBRT compared to baseline values (p=0.02). Fatigue at the 3-month follow-up and later were higher but not statistically significantly different compared to baseline. African-American patients reported higher fatigue post-SBRT than Caucasian patients. Fatigue was correlated with hormonal symptoms as measured by the Expanded Prostate Cancer Index Composite (EPIC) quality of life questionnaire, but not with urinary, bowel, or sexual symptoms. Age, co-morbidities, smoking, prostate specific antigen (PSA) levels, testosterone levels, and tumor stage were not associated with fatigue. Conclusion: This is the first study to investigate fatigue as a side-effect of SBRT. In contrast to standard radiation therapy, results suggest SBRT-related fatigue is short-term rather than a long-term side effect of SBRT. These results also suggest post-SBRT fatigue to be a more frequent complication in African-Americans than Caucasians.